2003
DOI: 10.1016/j.curtheres.2003.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-dose combination therapy with an angiotensin-converting enzyme inhibitor and a diuretic on flow-mediated vasodilation in hypertensive patients: a 6-month, single-center study

Abstract: Background: Combination therapy with an angiotensin-converting enzyme (ACE) inhibitor and a diuretic has been shown to be highly effective in hypertension. Clinical trials have demonstrated that ACE inhibitors may improve endothelial cell dysfunction in hypertension. However, the effectiveness of the combination treatment in endothelial cell dysfunction is unknown.Objective: This study investigated the effects of a new low-dose combination, perindopril 2 mg plus indapamide 0.625 mg, on brachial artery flow-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…We found that both hydrochlorothiazide and perindopril applied as hypertensive therapy to elderly subjects with essential hypertension effectively lowered blood pressure. Similar to other studies, 6,17,43,44 it was shown in the present study that diuretics and ACEI therapies are very efficient in the treatment of essential hypertension in elderly patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that both hydrochlorothiazide and perindopril applied as hypertensive therapy to elderly subjects with essential hypertension effectively lowered blood pressure. Similar to other studies, 6,17,43,44 it was shown in the present study that diuretics and ACEI therapies are very efficient in the treatment of essential hypertension in elderly patients.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, it is worth emphasizing that, in the present study, both perindopril and hydrochlorothiazide significantly increased NO concentrations. Sekuri et al 44 reported a significant improvement in endothelium function after treatment with perindopril and a diuretic (indapamide) applied in combination therapy. However, Higashi et al 8 stressed that ACEI exclusively could improve endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…The studies included in our meta-analysis were all RCTs, published until November 2020. The studies were conducted in Italy [ 12 19 ], Germany [ 20 ], China [ 21 26 ], Turkey [ 27 – 33 ], UK [ 34 ], Brazil [ 35 37 ], Greece [ 38 ], Denmark [ 39 ], Korea [ 40 45 ], Bulgaria [ 46 ], USA [ 47 ], Chile [ 48 ], and Japan [ 49 60 ]. A flow diagram depicting the inclusion process of these studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%